2021
DOI: 10.3389/feduc.2021.752199
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Students With School Refusal Behavior and Their Relationship to Learning Strategies

Abstract: Students with School Refusal Behaviour (SRB) are a diverse group, often associated with negative academic repercussions (e.g., low academic performance, learning difficulties or academic demotivation). The aims of this research were: 1) to identify school refusal behaviour profiles based on low and high scores on the four functional conditions assessed by the School Refusal Assessment Scale-Revised (SRAS-R) and 2) to examine the relationship between SRB profiles and learning strategies. The SRAS-R and the Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…The findings support the first study hypothesis, since four profiles were identified, which coincide with the most common groups of adolescent SRB found in previous literature (Delgado et al, 2019;Giménez-Miralles, Gonzálvez, Sanmartín et al, 2021;Gonzálvez, Kearney et al, 2018). Thus, participants with low, moderately high, and high levels of ANA, ESE, PAS, and PTR were grouped into the groups non-SRB, moderately high SRB, and high SRB, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The findings support the first study hypothesis, since four profiles were identified, which coincide with the most common groups of adolescent SRB found in previous literature (Delgado et al, 2019;Giménez-Miralles, Gonzálvez, Sanmartín et al, 2021;Gonzálvez, Kearney et al, 2018). Thus, participants with low, moderately high, and high levels of ANA, ESE, PAS, and PTR were grouped into the groups non-SRB, moderately high SRB, and high SRB, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Authors recruited samples with an age range of 12-18 years old. Except for two works with Latin American students Gonzálvez, Kearney et al, 2018), all of them were conducted in the Spanish population (Delgado et al, 2019;Giménez-Miralles, Gonzálvez, Sanmartín et al, 2021;. In respect of the profile solutions, these works coincide in finding a group characterized by low levels of ANA, ESE, PAS, and PTR, which has been predominantly called non-SRB.…”
Section: School Refusal Behavior In Adolescencementioning
confidence: 99%
See 2 more Smart Citations